2016
DOI: 10.1515/jtes-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Key Stakeholders’ Attitudes towards Teacher Education Programs in TEFL: A Case Study of Farhangian University in Iran

Abstract: Recently, teacher training courses have attracted the researchersí special attention, while teacher education programs have not received as much attention. The present study investigated the attitudes key stakeholders in a teacher education program (i.e., student teachers, in-service teachers, and teacher educators) hold toward the appropriateness of TEFL teacher education programs at an Iranian teacher education university and their relevance to and sustainable impact in the real teaching context. To this end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
1
20
0
2
Order By: Relevance
“…To exemplify, the results of the study bear similarities with those of Gholami and Qurbanzada (2016) in terms of the importance and increased need of practical courses that are considered to prepare student teachers for real teaching environments and help them continue sustainability in their professional lives. In parallel with Pehkonen and Turner (1999), contextual factors like the school setting, administration, student profile and parental involvement were found to affect professional skills of teachers but no participant mentioned the impact of contextual factors on research skills, which could be due to their lacking research skills or work overload to cover the curriculum.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To exemplify, the results of the study bear similarities with those of Gholami and Qurbanzada (2016) in terms of the importance and increased need of practical courses that are considered to prepare student teachers for real teaching environments and help them continue sustainability in their professional lives. In parallel with Pehkonen and Turner (1999), contextual factors like the school setting, administration, student profile and parental involvement were found to affect professional skills of teachers but no participant mentioned the impact of contextual factors on research skills, which could be due to their lacking research skills or work overload to cover the curriculum.…”
Section: Discussionmentioning
confidence: 79%
“…Since sustainability is a tool of continuous progression, it is important to reveal and compare the opinions of different groups of stakeholders who have a say and shape the content and route of teacher education programs. Likewise, Gholami and Qurbanzada (2016) examined the perspectives of 62 pre-service teachers, 48 in-service teachers, and 28 teacher educators in Iranian context at TEFL (Teaching English as Foreign Language) departments. What was stressed by all the three groups of participants was the existence of practical courses such as methodology in TEFL program and courses like practicum and classroom observations were reported to empower teachers for real educational settings.…”
Section: Sustainable Development In Teacher Educationmentioning
confidence: 99%
“…The study provided some pedagogical implications directed toward sustainable professional development. Gholami and Qurbanzada (2016) found out that in-service teachers had a negative perspective towards the impractical courses which tended to be not practical in the real classroom environment and they regarded them as less powerful. The participants of the study found courses related to teaching like teaching methodology, of special sustainable nature and beneficial in the actual teaching context.…”
Section: Research On the In-service Teacher Training And The Continuimentioning
confidence: 99%
“…Buczynski & Hansen, 2010;Chang, Jeon, & Ahn, 2014;Hung & Yeh, 2013;Kumba & Nkumbi, 2008;Powell, Terrell, Furey, & Scott-Evans, 2003;Smith & Gillespie, 2007;Tang, Lee, & Chun, 2012). Yet, the beliefs of EFL teachers about CPD have been largely ignored (Gholami & Qurbanzada, 2016;Pipere, Veisson, & Salite, 2015).…”
Section: Introductionmentioning
confidence: 99%